(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2025)
The British administration in Malaya argued that the Malay Reservations Enactment 1913 aimed to safeguard the land rights of Malays. It was believed that Malay land rights were endangered by the prevalent practice of selling and mortgaging land to foreigners for quick profit among the Malays. Consequently, the enactment was introduced to protect and consolidate Malay land rights. However, this article contends that the formulation of this enactment not only failed to secure Malay land rights consistently but also served to mask the shortcomings of British law and land administration under the Land Enactment of 1911. This legislation was later replaced by the Land Code 1926, which further exacerbated the issue and contributed significantly to the loss of land among the Malays. Despite the existence of the Malay Reservations Enactment 1913, British land laws and administration posed challenges for Malays in maintaining existing land ownership and acquiring new land. Therefore, the enactment proved ineffective in preventing Malays from losing their land. This article employs a historical method that focuses on primary resources. The primary resources referred to are colonial records, specifically the Perak Government Gazettes, Annual Reports of Perak, Malayan Agricultural Journal and Year Book and Manual of Statistics.